Fungal Systematics and Evolution: FUSE 3 - Krisai-Greilhuber, Irmgard; Chen, Yun; Jabeen, Sana; Madrid, Hugo; Marincowitz, Seonju; Razaq, Abdul; Ševčíková, Hana; Voglmayr, Hermann; Yazici, Kenan; Aptroot, André; Aslan, Ali; Boekhout, Teun; et al. (Sydowia, 2017)
The present study introduces seven new species, one new combination, one new variety and several interesting taxonomical notes and/or geographical records. Most of the new taxa are Ascomycetes, but the study also includes a new variety of a Basidiomycete. Novel species include Gyromitra khanspurensis (Discinaceae, Pezizales, Pezizomycetes) from Pakistan growing near Cedrus deoadara and Paramyrothecium guiyangense and Paramyrothecium verruridum (Stachybotriaceae, Hypocreales, Sordariomycetes) both isolated from soil in China. New species from South Africa are Sclerostagonospora elegiae on culm litter of Elegia equisetacea, Sclerostagonospora fusiformis on culm litter of Thamnochortus spicigerus, Sclerostagonospora pinguis on culm litter of Cannomois virgata and Sclerostagonospora sulcata on culm litter of Ischyrolepis subverticellata (Phaeosphaeriaceae, Pleosporales, Dothideomycetes). Hapalocystis berkeleyi var. kickxii with its basionym Hypoxylon kickxii is shown to be a taxon on species level and thus recombined as Hapalocystis kickxii (Sydowiellaceae, Diaporthales, Sordariomycetes), and it is lecto- and epitypified. The new variety Pluteus romellii var. luteoalbus (Pluteaceae, Agaricales, Agaricomycetes) growing on a mossy fallen stem of a deciduous tree is described from Czech Republic. Cortinarius scaurocaninus (Cortinariaceae, Agaricales, Agaricomycetes) is new for Austria, Humicola grisea (Chaetomiaceae, Sordariales, Sordariomycetes) is an interesting new record for Chile. Two taxa are reported as new for Turkey: the lichenicolous fungus Opegrapha parasitica (Opegraphaceae, Arthoniales, Arthoniomycetes) growing partly immersed in the thallus of Aspicilia and the lichen Rinodina zwackhiana (Physciaceae, Teloschistales, Lecanoromycetes) from calcareous rock. Finally, Xerula strigosa (Physalacriaceae, Agaricales, Agaricomycetes), described from China, is confirmed to be present also in Pakistan.
Keywords: biodiversity; ITS barcodes; phylogeny; systematics